O determinante demonstrativo em sintagmas nominais - Graziela Zamponi (Cadernos de Estudos Lingüísticos, 2011)
In this paper we start a reflection about demonstrative noun phrases. From the concept of memorial deixis, we infer the presence of an associated “subjectivity” in the use of demonstrative determiners, through which the speaker calls the addressee’s attention to an object, therefore giving a discursive dimension to this type of determiner.